Professional practice of applied performance analysis - Martin, D. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
Applied performance analysts (PAs) are a well-established applied sports science practitioner group, embedded under various titles in the majority of the world`s elite sports performance ecosystems. However, there has been little investigation of the nature of their professional practice within applied environments, or if performance analysis does indeed constitute a profession. This presentation will consider the evolution of applied practice within performance analysis as it has evolved to keep pace with technological developments and the emergence of big data. The presentation will focus on three key strands; 1) Harnessing data to co-create insights and ultimately value within performance ecosystems; 2) The current status of applied performance analysts as professionals; 3) Performance Analysis 3.0: future directions for the profession. Given the huge investment by sports performance organisations in the technology and human resources to generate performance data it is pertinent to pause and consider the value these data create, how value is created and for whom. Recent studies suggest that value is co-created between analysts and coaches; the analyst team generate, curate and translate insights based on the direction and guidance of the coaching or executive staff. It is becoming clear that while analysts need domain and technical knowledge, they also need particular personal attributes and professional behaviours to allow them develop the contextual intelligence required to deliver a valued service. Investigations which have captured the lived experiences of applied PAs reveal a group of dedicated and passionate practitioners who face several challenges including general role ambiguity, ad-hoc recruitment and job insecurity, poor working conditions, widespread use of unpaid internships and poor salaries, continually having to `prove their worth` in an often volatile micro-political climate, and a general uncertainty about what skill set is required as the profession and technology rapidly evolve. There is an opportunity to re-imagine and rebrand to `Performance Analysis 3.0` with a clear role definition, professional regulation, and a development pathway for applied professional practitioners. This presentation will be of interest to attendees engaged in the application of performance data in applied environments; analysts, coaches, and sports scientists. It will also appeal to delegates involved in professional development, reflective practice and accreditation.